Correlation of growth inhibition with accumulation of Pb in cell wall and changes in response to oxidative stress in Arabidopsis thaliana seedlings - Phang, Ing Chia; Leung, David W. M.; Taylor, H. Harry; Burritt, David J. (Springer Science+Business Media B.V., 2010)
Uptake of the non-essential element, lead (Pb), by 7-days-old Arabidopsis thaliana seedlings caused inhibition of root growth. Pb accumulated mainly in the root and only a small proportion of the total uptake was transported to the shoot. At the ultrastructural level, Pb was localized mainly in the cell walls, intercellular spaces and vacuoles, which may serve to minimize Pb toxicity to vital functions of the cytosol. Pb exposure induced the generation of reactive oxygen species (ROS) and increased the level of lipid hydroperoxide. These changes were accompanied by up-regulation of the activities of antioxidative enzymes in a dose-dependent manner. Although no major destructive changes to the cytoplasm and vital organelles were observed, it is postulated that at least part of the cost of Pb exposure to A. thaliana seedlings is reflected in reduced root growth associated with increased free radical production by cell wall-accumulated Pb.